2020
DOI: 10.21203/rs.3.rs-82519/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Desulfurization of Vulcanized Rubber Particles Using Biological and Chemical Methods

Abstract: Currently, recycling or degradation treatments for tires are an enormous challenge. Despite efforts to dispose of or recycle it, rubber waste is increasing year by year worldwide. To create a rubber-recycling system, several researchers have proposed tire desulfurization. In this study, we compare two methods: one biological, using Acidobacillus ferroxidans in shake 250 mL flask experiments, and one chemical using, for the first time, microwaves and an aqueous solution. The results of these methods were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In the same study the selectivity of samples treated at 140-160 • C was much improved but the decrease in the crosslink density was only moderate. Another study showed promising desulfurization rates at temperatures of 200 • C or more, but again also experienced shortening of the polymer as a result of C-C bond breakage (Valdés et al, 2021). Another apparent limitation of the microwave method is that only rubber with sufficient polarity is susceptible to the microwave radiation (Asaro et al, 2018).…”
Section: Microwave Reclamationmentioning
confidence: 99%
“…In the same study the selectivity of samples treated at 140-160 • C was much improved but the decrease in the crosslink density was only moderate. Another study showed promising desulfurization rates at temperatures of 200 • C or more, but again also experienced shortening of the polymer as a result of C-C bond breakage (Valdés et al, 2021). Another apparent limitation of the microwave method is that only rubber with sufficient polarity is susceptible to the microwave radiation (Asaro et al, 2018).…”
Section: Microwave Reclamationmentioning
confidence: 99%
“…Progress in biobased rubber has been reported [ 20 , 21 , 22 ]. Moreover, interesting research has been carried out on rubber desulfurization [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%